MATHEMATICAL MODELLING OF SCALING IN A RESERVOIR WHICH CONTAINS IMPERMEABLE LAYERS - Bedrikovetsky, P.; Rosario, F.; Bezerra, M.; Silva, M.; Lopes Jr., R. (Revista de Engenharia Térmica, 2002)
Several different scenario of injected and reservoir water mixing have been proposed: mixing at high velocity near to injectors, mixing at low velocity inside reservoirs, mixing by diffusion via boundaries of layers with different permeabilities, mixing of injected, connate and aquifer waters at high velocity near to producers. Just the latter mechanism results in the accumulation of formation damage, while other mechanisms cause precipitation near to moving concentration front. In the current paper a new mechanism of oilfield scaling by diffusion of Barium from impermeable layer into the reservoir is proposed. The mechanism results in accumulation of precipitant and of formation damage. Viscous dominant regime of waterflooding takes place in the majority of oil fields. The Welge´s method allows calculating the permeability distribution from water cut history. The proposed extension to Welge´s method determines the partition of permeable layers in a reservoir from tracer concentration in production wells. Knowledge of this partition is important for modelling of oilfield scaling accounting for Barium supply from impermeable layers.